Investigation of the Phase Transformation in Hot Stamping Processes with Regard to the Testing Facility - Horn, Alexander; Hart-Rawung, T.; Buhl, J.; Bambach, Markus; Merklein, Marion (Congress of the German Academic Association for Production Technology WGP 2021, 2020)
Hot stamping of boron manganese steel is a state of the art process for manufacturing safety-relevant automotive components with regard to lightweight design. In terms of the mechanical properties, the microstructural evolution is of particular interest. Besides conventional hot stamping processes, this is especially apparent for the manufacture of hot stamped parts with tailored properties. To reduce costs and scrap parts, numerical process design requires appropriate material models considering transformation kinetics during in-die quenching. The phase transformation behavior can be characterized through experiments on various testing facilities, which can lead to discrepancies in the results and therefore in the predicted mechanical properties. In this paper, the results from two testing facilities are compared to each other through dilatometry experiments on the boron-manganese steel 22MnB5. For further characterization of the differences, secondary samples are taken to analyze the hardness as well as the microstructure by optical microscopy.
Keywords: Hot stamping; Dilatometry test; Phase transformation